Distribution of carbon, nitrogen and phosphorus in a moss community‐soil system developed on a cold desert in Antarctica - Ino, Yoshio; Nakatsubo, Takayuki (Ecological Research, 1986)
Abstract The distributions of carbon, nitrogen and phosphorus in a moss community‐soil system developed on a naked region in Rundvågskollane (69 0 50'S, 39 0 09'E), East Antarctica, were investigated in order to analyze the flow of matter in an Antarctic terrestrial ecosystem. The moss community was formed from many moss blocks of different sizes and was composed of Bryum pseudotriquetrum (Hedw.) Gaertn., Meyer et Scherb., Ceratodon purpureus (Hedw.) Brid. and Grimmia lawiana J. H. Willis. The surface of the community was covered with cyanobacteria. It was estimated that nitrogen fixed by cyanobacteria flowed from these organisms to the moss and that little nitrogen was transported within the moss body. A large amount of phosphorus existed in the soil. The moss community had a high phosphorus content although the amount itself was relatively little due to the small phytomass. It seems that absorption of phosphorus from soil is difficult for moss, because of the paucity of water necessary for the movement of phosphorus and the suppressed growth of moss due to the arid conditions.